Análisis Termogravimétrico y Estudio Cinético de la Pirólisis de Residuos Sólidos Veterinarios - Rojas González, Andrés Felipe; Aranzazu Río, Laura María (Ingeniería, 2016)
Context: Institutional waste from clinical centers can be classified as those coming from health institutions dedicated to human attention and those coming from centers for animal veterinary care. The latter are mainly hazardous wastes, hence their disposal requires incineration. Most of such waste is organic, and it is possible, therefore, to take advantage of their energetic power in combustion or pyrolysis processes. This work is motivated because no literature was found on the pyrolysis kinetics veterinary waste, as this kind of studies are mainly focused on hospital waste of human health care. Method: The kinetics of pyrolysis is characterized and studied by means of thermogravimetric analysis of 6 major veterinary waste (gauze, cotton swabs, cotton, nails, hair, plastic syringes). The characterization is performed by proximate and elemental analysis, and thermogravimetric analysis. Reactivity characteristics and pyrolytic capability of wastes are established. The kinetics study on pyrolysis was carried out by determining the kinetic triplet by isoconversional Starink method. Results: It was established that the pyrolysis index increases with the heating rate and that the thermal degradation depends on the material type of the waste. Similarly, it was found that the temperature (ΔT = Tf - Ti) for the thermal decomposition of veterinary waste is: ΔTnails> ΔThair > ΔTcotton swabs > ΔTgauze > ΔTcotton > ΔTplastic syringes; the activation energy is Enails> E hair > Eplastic syringes > Ecotton swabs > E gauze > Ecotton, and the reaction order is: n hair > nnails > ncotton swabs > ncotton > n gauze > n plastic syringes. Conclusions: These results suggest the possibility of using veterinary wastes for power generation, providing an alternative for sustainable energy development to cities in continuous growth, from both, energetic and environmental points of view.